Asymmetric vinylogous mannich reaction of silyloxy furans with N-tert-butanesulfinyl ketimines - Rao, V. U. Bhaskara; Jadhav, Amol P.; Garad, Dnyaneshwar N.; Singh, Ravi P. (Organic Letter, 2014)
A highly regio- and diastereoselective TMSOTf promoted vinylogous Mannich reaction for the synthesis of chiral quaternary 3-aminooxindole butenolides from 2-silyloxy furans and chiral ketimines is described. The method is found to be very efficient and also provides a facile access to sterically challenging 3-aminooxindole butenolides bearing two quaternary centers in continuation. Further, the versatility of the method is demonstrated by the 1,4-addition of nucleophiles on the sterically congested butenolide substructure..

Radical-mediated dehydrative preparation of cyclic imides using (NH4)(2)S2O8-DMSO: application to the synthesis of vernakalant - Garad, Dnyaneshwar N.; Tanpure, Subhash D.; Mhaske, Santosh B. (Beilstein Journal of Organic Chemistry, 2015)
Ammonium persulfate-dimethyl sulfoxide (APS-DMSO) has been developed as an efficient and new dehydrating reagent for a convenient one-pot process for the synthesis of miscellaneous cyclic imides in high yields starting from readily available primary amines and cyclic anhydrides. A plausible radical mechanism involving DMSO has been proposed. The application of this facile one-pot imide forming process has been demonstrated for a practical synthesis of vernakalant.
Keywords: APS-DMSO; imides; practical synthesis; radical-mediated; vernakalant

Pd(II)-catalyzed intramolecular tandem olefin amidation/C-H activation protocol for the syntheses of the protoberberine class of natural products - Garad, Dnyaneshwar N.; Mhaske, Santosh B. (Organic Letters, 2016)
A Pd(II)-catalyzed intramolecular tandem olefin amidation/C-H activation protocol has been developed for the synthesis of an 8-oxoprotoberberine core. It was successfully applied for the syntheses of (+/-)-8-oxocanadine, (+/-)-8-oxotetrahydropalmitine, and (+/-)-8-oxostylopine, which can be easily converted to the respective protoberberine natural products. The short synthetic route demonstrated would be useful for the synthesis of a large number of natural products and their analogues featuring a protoberberine scaffold.

Diversification of quinazolinones by Pd-catalyzed C(sp(3))-acetoxylation - Garad, Dnyaneshwar N.; Mhaske, Santosh B. (Journal of Organic Chemistry, 2017)
The quinazolinone ring has been exploited as a directing group for C(sp(3))-H functionalization for the first time. The proximal C-gamma(sp3)-H bonds have been oxidized by palladium-catalyzed acetoxylation reaction. Various functional groups on the quinazolinone scaffold were tolerated to provide novel quinazolinone derivatives. The use of base was found to be crucial for the mono selective acetoxylations.

Pd-catalyzed regioselective mono-arylation: quinazolinone as the inherent directing group for C(sp(2))-H activation - Garad, Dnyaneshwar N.; Viveki, Amol B.; Mhaske, Santosh B. (Journal of Organic Chemistry, 2017)
The Pd-catalyzed quinazolinone-directed regioselective monoarylation of aromatic rings by C-H bond activation is developed. A broad substrate scope is demonstrated for both quinazolinone as well as diary-liodonium triflates. The use of a base was found to be crucial for this transformation, unlike for the known nitrogen-directed arylations. All of the novel quinazolinones of biological interest were synthesized by using the operationally simple Pd(II)-catalyzed arylation reaction.
Keywords: Aromatic rings; catalysis; Chemical activation; Chemical reactions; Palladium compounds; Regioselectivity

Ru-catalyzed regioselective cascade annulation of acrylamides with 2-alkynoates for the synthesis of various 6-Oxo nicotinic acid esters - Garad, Dnyaneshwar N.; Mhaske, Santosh B. (Journal of Organic Chemistry, 2019)
Ru-catalyzed regioselective cascade annulation of acrylamides with 2-alkynoates via aza-Michael/C-H activation sequence for the synthesis of various 6-oxo nicotinic acid esters is described. The regioselectivity of the protocol has been confirmed by performing silver mediated protodecarboxylation of the corresponding 6-oxo nicotinic acid to furnish 2-pyridone. The developed protocol is copper or silver salt-free and uses inexpensive, safe, and environmentally benign peroxide-based ``oxone'' as the sole oxidant. A redox-neutral version of the protocol is also demonstrated.

Para-selective copper-catalyzed C(sp(2))-H amidation/dimerization of anilides via a radical pathway - Viveki, Amol B.; Garad, Dnyaneshwar N.; Gonnade, Rajesh G.; Mhaske, Santosh B. (Chemical Communications, 2020)
Copper-catalyzed amidation/dimerization of anilides via regioselective C(sp(2))-H functionalization is achieved. The para-selective amidation is accomplished on the anilide aromatic ring via a radical pathway leading to C-N bond formation in the presence of ammonium persulfate as a radical source/oxidant for the copper catalyst. The developed protocol tolerates a wide range of anilide substrates. The regioselectivity is confirmed by single-crystal X-ray studies.